Structural Modification of Bentonite by Rice Husk Biochar for Enhanced Methylene Blue Removal under Visible Irradiation - Neza Rahayu Palapa; Elsa Irma Esthomihi Manurung; Yulizah Hanifah; Davin Philo (Science and Technology Indonesia, 2026)
The development of sustainable and low-cost materials for wastewater treatment remains an important environmental challenge. In this study, a bentonite-biochar (Bnt–Bc) composite was prepared through structural modification of bentonite using rice husk–derived biochar followed by KOH-assisted activation. The physicochemical properties of the materials were systematically characterized using XRD, BET, FTIR, SEM, and UV–Vis diffuse reflectance spectroscopy. The results revealed that biochar incorporation modified the interlayer structure of bentonite, resulting in reduced crystallinity, pore structure alteration, and the introduction of additional oxygen-containing functional groups. These structural changes contributed to improved surface reactivity and enhanced interaction with dye molecules. The performance of the materials was evaluated for methylene blue (MB) removal under Visible Light irradiation. The Bnt–Bc composite exhibited significantly higher removal efficiency compared to pristine bentonite and biochar, achieving up to 98% MB removal within 150 min. Kinetic analysis indicated that the removal process followed a pseudo-first-order model. The enhanced performance is attributed to the combined effects of improved adsorption capacity, surface functional groups, and photo-assisted degradation under Visible Light irradiation. This study demonstrates that biochar modified bentonite composites derived from agricultural waste represent a promising and environmentally friendly material for dye-contaminated wastewater treatment.